IMPLEMENTASI NILAI-NILAI PANCASILA MELALUI MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DALAM PEMBENTUKAN KARAKTER PEDULI SOSIAL SISWA KELAS VII.A SMP NEGERI 3 SOLOK SELATAN - Aria Gustari; Budi Juliardi, Reindy Rudagi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of Pancasila values through the Pancasila and Citizenship Education (PPKn) subject in developing a socially conscious character in grade VII.A students at SMP Negeri 3 Solok Selatan. The study used a descriptive qualitative method, with a PPKn teacher and 28 students as subjects. Data were obtained through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing.The results indicate that the implementation of Pancasila values is carried out through the integration of learning materials, active methods such as discussions and case studies, habituation of attitudes outside the classroom, and teacher role models. The impact is seen in increased student participation in social activities, concern for peers, and responsibility for protecting the environment. Challenges encountered include differences in student backgrounds, limited time, and lack of parental support. Keywords: Nilai Pancasila, PPKn, Karakter Peduli Sosial